ANALYSIS OF PANGIA VILLAGE POPULATION DATA PROCESSING, HELUMO DISTRICT, BOLAANG MONGONDOW SELATAN DISTRICT - mulyadin lauhi; Ely Ibrahim; Sitti Husna Noviana Djou (Governance: Jurnal Ilmu Administrasi Publik, 2024)
This study aims to analyze the population data processing system in Pangia Village, Helumo District, South Bolaang Mongondow Regency. The research employs a qualitative descriptive method, with data collected through direct observation, interviews, and documentation. Three informants were selected to provide comprehensive insights into the village's administrative processes. The results indicate that while population data processing in Pangia Village is generally functional, significant improvements are required in specific areas. The primary challenges identified include the limited quality of human resources and inadequate supporting infrastructure. However, other management indicators suggest that the basic administration of resident data has been handled with a satisfactory level of consistency.